2011
DOI: 10.1021/es202565g
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Selenium Reduces Retention of Methyl Mercury in Freshwater Fish

Abstract: Adverse effects from organic mercury transported along aquatic food chains are health issues in humans and other top predators. Methyl mercury in organisms at the lower food chain levels is eliminated slowly, and laboratory studies have not clarified the role of selenium in the retention of methyl mercury in fish. Here, we investigated the effects of dietary selenium on the retention of organic and inorganic mercury in freshwater fish. Addition of selenite to the food augmented elimination of methyl mercury (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 42 publications
4
43
1
Order By: Relevance
“…Furthermore, the [Se] in liver tissues of O. mykiss (average 23 and 26 μg g −1 DW in ME and MW respectively) and S. trutta (10 μg g −1 DW) was 2 to 6 times higher than those in the species with higher muscle [THg] P. trucha and S. fontinalis (average 4.1 to 4.4 μg g −1 DW), associated probably with higher Se dietary uptake. These results could be consistent with the protective effect of Se to explain the low muscle [THg] in O. mykiss and S. trutta adults (Belzile et al, 2009;Peterson et al, 2009a,b;Sørmo et al, 2011), especially in light of recent evidence showing increased elimination of MeHg with increased Se intake in freshwater fish (Bjerregaard et al, 2011).…”
Section: Large Fishsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the [Se] in liver tissues of O. mykiss (average 23 and 26 μg g −1 DW in ME and MW respectively) and S. trutta (10 μg g −1 DW) was 2 to 6 times higher than those in the species with higher muscle [THg] P. trucha and S. fontinalis (average 4.1 to 4.4 μg g −1 DW), associated probably with higher Se dietary uptake. These results could be consistent with the protective effect of Se to explain the low muscle [THg] in O. mykiss and S. trutta adults (Belzile et al, 2009;Peterson et al, 2009a,b;Sørmo et al, 2011), especially in light of recent evidence showing increased elimination of MeHg with increased Se intake in freshwater fish (Bjerregaard et al, 2011).…”
Section: Large Fishsupporting
confidence: 84%
“…Selenium has a high chemical affinity with Hg in biological systems and can form insoluble Hg-Se complexes, sequestering Hg from the biological processes and neutralizing its toxic effects (Belzile et al, 2009;Khan and Wang, 2009;Peterson et al, 2009a,b;Sørmo et al, 2011). Elevated dietary Se has been linked with increased elimination of MeHg in freshwater fish (Bjerregaard et al, 2011). Therefore, the dual study of Se and Hg transfer in aquatic food webs is important to ascertain the potential impact of Hg in the ecosystem and the processes of Hg food web dynamics in a given aquatic system.…”
Section: Introductionmentioning
confidence: 99%
“…In the only other polar bear study involving hormones and mercury, Knott et al (2011a) found circulating concentrations of selenium (Se) to be higher in Southern Beaufort Sea males than females. This is interesting because other studies suggest that Se may act as an antioxidant if present in high enough concentration, protecting wildlife from the toxicological effects of methylmercury and aiding in excretion of the compound (Ralston and Raymond 2010;Bjerregaard et al 2011). If the findings of Knott et al (2011a) hold true for WH bears as well, it may help explain the lower mercury concentrations we found in male polar bears.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have shown that Se could effectively protect against the toxicity of AFB 1 [2], Cd [8], and mercury [9]. AFB 1 -induced toxic effects are closely associated with oxidative stress, which can destroy the liver and mitochondrial function [2,5].…”
Section: S Liaomentioning
confidence: 99%